2020
DOI: 10.2174/1874205x02014010053
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations Associated with Synthetic Cannabinoid Use- A Case Series

Abstract: Background: Synthetic Cannabinoid (SC) use has emerged as a growing public health threat in the United States. Several unexpected cases, presenting with a constellation of unrelated symptoms, but all having toxicity linked to SC use, have been reported in the last decade (2010-2019). Methods: We report a cluster of several independent cases where patients were admitted having different neurological manifestations. Extensive and expensive work-ups were performed. Upon further inspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…To the best of our knowledge, there have been no reports of ADEM caused by chronic cannabis abuse, though Samra et al reported ADEM in a healthy 25-year-old man after using a synthetic cannabinoid called Black Mamba [ 9 ]. Other cases of neurological diseases associated with synthetic cannabinoid use have also been reported, though the causative mechanism in those patients was unknown [ 10 ]. However, a growing body of research suggests that chronic cannabinoid exposure, particularly during adolescence, can have neurotoxic effects on developing white matter, resulting in decreased white matter coherence, though the physiopathology is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no reports of ADEM caused by chronic cannabis abuse, though Samra et al reported ADEM in a healthy 25-year-old man after using a synthetic cannabinoid called Black Mamba [ 9 ]. Other cases of neurological diseases associated with synthetic cannabinoid use have also been reported, though the causative mechanism in those patients was unknown [ 10 ]. However, a growing body of research suggests that chronic cannabinoid exposure, particularly during adolescence, can have neurotoxic effects on developing white matter, resulting in decreased white matter coherence, though the physiopathology is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A vasculotropic and epitheliotropic pattern of inflammation may be seen in some cases, but this is not etiologically specific and overlaps with other, more common inflammatory liver diseases. Although identification of spirochetes in the tissue by special stain or immunohistochemistry is diagnostic in the appropriate setting (11), false negative staining is not uncommon in the setting of disseminated treponemal disease, reaffirming the need for close clinicopathologic correlation to make the diagnosis in most cases. In the absence of known or reported risk factors for SH, the diagnosis is likely to be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Heightened clinical awareness and recognition of patients at risk for the disease are necessary to facilitate timely diagnosis and treatment. Risk factors including unprotected sexual activity, polysubstance abuse and IDU attribute to notably high rates of coinfection, increased hospital costs and a massive burden on the healthcare system ( 2 , 12 , 13 ). The incidence of primary and secondary syphilis are on the rise ( 1 ), and the identification and treatment of syphilis cases prevents progression to tertiary syphilis in affected individuals and the spread to other individuals.…”
Section: Discussionmentioning
confidence: 99%